Effect of changing temperature trends on relative humidity trends in Sirte. For period (1970-2009) (مجلة جامعة سرت للعلوم الانسانية, 2023)
This study aims at recognizing and analyzing the Effect of Change in the Trend of Annual Maximum, Minimum & Normal Averages of Temperature in the Trend of Relative Humidity Annual Averages in SIRTE within the period (1970 – 2009) by applying the analytical methodology & Quantitative method through the use of statistical methods, namely: The Moving Averages, Simple Linear Regression & T- Test in dealing with study data.The study concluded to the existence of the general trend to rise in annual averages of maximum, minimum, and normal temperature in addition to the existence of the general trend in rise of annual averages of relative humidity. This reflects the impact on values of annual averages of relative humidity, especially after 1990, by local effects represented in unroofed water reservoirs of the Man-Made River Project which had already been constructed in the area of the study and the most important of which are AlGurdabiya Reservoirs and those reservoirs constructed on the farm of the area.
Keywords: Temperatures; Relative Humidity; Moving Averages; Sirte